2015
DOI: 10.1155/2016/7420637
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Oxidative Stress, Circadian Rhythms, and AMD

Abstract: This work reviews concepts regarding oxidative stress and the mechanisms by which endogenous and exogenous factors produce reactive oxygen species (ROS). It also surveys the relationships between oxidative stress, circadian rhythms, and retinal damage in humans, particularly those related to light and photodamage. In the first section, the production of ROS by different cell organelles and biomolecules and the antioxidant mechanisms that antagonize this damage are reviewed. The second section includes a brief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 179 publications
(197 reference statements)
0
58
0
1
Order By: Relevance
“…Oxidative damage to lipids and DNA in bipolar patients has also been observed in both the brain and serum . 8‐ISO and 4‐HNE were found to be increased in the postmortem prefrontal cortex from patients with BD when compared with controls .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Oxidative damage to lipids and DNA in bipolar patients has also been observed in both the brain and serum . 8‐ISO and 4‐HNE were found to be increased in the postmortem prefrontal cortex from patients with BD when compared with controls .…”
Section: Discussionmentioning
confidence: 94%
“…8‐ISO and 4‐HNE were found to be increased in the postmortem prefrontal cortex from patients with BD when compared with controls . In addition, clinical research has also demonstrated elevated levels of lipid peroxidation in the serum of bipolar patients . Interestingly, Versace and colleagues demonstrated a relationship between white matter damage and peripheral lipid peroxidation in bipolar patients.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Recently, free radicals have been investigated as an emerging therapeutic target for the treatment of neurological disorders including Alzheimer's disease and ALS, 41 as well as ocular diseases such as glaucoma, diabetic retinopathy, and age-related macular degeneration. [42][43][44] Thus, VPA, as well as edaravone, seems to be a suitable candidate for drug repurposing for neurotrauma. We also showed that administration of edaravone was effective even after ONI, strongly suggesting the possibility that edaravone is a potential drug for treatment of optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions in ARMD are located in the macula, the central and posterior portion of the retina that includes the RPE and photoreceptors. The disease is characterized by the accumulation of drusen, which are abnormal extracellular deposits along the basal layer of the RPE 13,23,24, and drusen deposition is correlated with RPE damage and the degeneration of photoreceptors. Another pathologic feature of ARMD is the accumulation of debris known as lipofuscin in the lysosomes of RPE cells.…”
Section: Introduction To Autophagymentioning
confidence: 99%
“…Another pathologic feature of ARMD is the accumulation of debris known as lipofuscin in the lysosomes of RPE cells. Lipofuscin, which is a heterogeneous mixture of lipoproteins, sensitizes RPE cells to light exposure and induced oxidative stress, eventually resulting in further protein misfolding 13,23,24.…”
Section: Introduction To Autophagymentioning
confidence: 99%